ESTIMULANTES DE CRESCIMENTO NA PRODUT IVIDADE DE CULTIVARES DE SOJA - CEOLIN, ergio Everton Nascimento; GRAICHEN, Felipe André Sganzerla; CAVALCANTI, ittor Gomes; DE BULNES, Vinícius Fermiano; SILVA, Marcos Henrique de Lima; DE MOURA, Daniel Bezerra (ANAIS DO ENIC, 2017)
-